Bigheaded Ant, Pheidole megacephala (Fabricius) (Insecta: Hymenoptera: Formicidae: Myrmicinae) - John Warner; Rudolf H. Scheffrahn (EDIS)
EENY-369, a 7-page illustrated fact sheet by John Warner and Rudolf H. Scheffrahn, describes this successful invasive soil-nesting ant that is considered a threat to native ants and is among 100 of the "World's Worst" invaders. Includes sections on distribution, description, similar ants in Florida, life cycle, foraging and feeding, nest sites, pest status, management and selected references. Published by the UF Department of Entomology and Nematology, January 2007.